2020
DOI: 10.3390/jcm9092714
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlations in Children with HHT

Abstract: Hereditary hemorrhagic telangiectasia (HHT), a rare autosomal dominant disease mostly caused by mutations in three known genes (ENG, ACVRL1, and SMAD4), is characterized by the development of vascular malformations (VMs). Patients with HHT may present with mucocutaneous telangiectasia, as well as organ arteriovenous malformations (AVMs) of the central nervous system, lungs, and liver. Genotype–phenotype correlations have been well described in adults with HHT. We aimed to investigate genotype–phenotype correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…By contrast, patients who have an ACVRL1 mutation (HHT2) have HAVMs more frequently, and PAVMs are rare. There are many reports concerning genotype-phenotype correlations of HHT in which the gender difference is important ( 2 , 7 ). Letteboer et al ( 2 ) reported that in HHT1, only 1 of 56 male patients had HAVMs, whereas 9 of 88 female patients had HAVMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, patients who have an ACVRL1 mutation (HHT2) have HAVMs more frequently, and PAVMs are rare. There are many reports concerning genotype-phenotype correlations of HHT in which the gender difference is important ( 2 , 7 ). Letteboer et al ( 2 ) reported that in HHT1, only 1 of 56 male patients had HAVMs, whereas 9 of 88 female patients had HAVMs.…”
Section: Discussionmentioning
confidence: 99%
“…Letteboer et al ( 2 ) reported that in HHT1, only 1 of 56 male patients had HAVMs, whereas 9 of 88 female patients had HAVMs. Kilian et al ( 7 ) reported that only 1 of 101 male children with HHT1 had HAVMs. Interestingly, Dupuis-Girod et al ( 8 ) published an article that demonstrated the effectiveness of bevacizumab in the treatment of high-output HF due to HAVM.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the HHT subtype can be identified and first-degree relatives can be tested for the disease. HHT is estimated to affect approximately 1 in 5000–6000 Europeans [ 7 , 8 ]. More than 76–80% of all cases of HHT are due to mutations in either ENG or ACVRL1 [ 9 , 10 ].…”
Section: Hht Diagnosismentioning
confidence: 99%
“…[ 1 ] Its primary pathogenic expression is multiple arteriovenous malformations (AVM), especially in lungs, liver, brain, and rarely the spine. [ 2 ] The incidence is 1:5000–1:10000 worldwide. [ 2 ] Common manifestations are telangiectases, reported in 74% of patients,[ 3 ] in nasal mucosa, gastrointestinal tract, lips, and hands.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The incidence is 1:5000–1:10000 worldwide. [ 2 ] Common manifestations are telangiectases, reported in 74% of patients,[ 3 ] in nasal mucosa, gastrointestinal tract, lips, and hands. Over 90% of all HHT patients present chronic epistaxis due to nasal telangiectases by the age of 45 years.…”
Section: Introductionmentioning
confidence: 99%